The sandlot [videorecording (DVD)] - Evans, David Mickey; Guiry, Thomas, 1981-; Vitar, Mike, 1978-; Renna, Patrick, 1979-; Leopardi, Chauncey, 1981- (20th Century Fox Home Entertainment, 2017)
Fifth-grader Scotty Smalls has just moved into town with his parents. The local kids call him a Dork because he can't even throw a baseball. That changes when the leader of the neighborhood gang recruits him to play on the nearby sandlot field. It's the beginning of a magical summer of baseball, wild adventures, first kisses, and fearsome confrontations with the dreaded Beast and its owner who live behind the left field fence. Soon nine boys have become best friends, Scotty is part of a team, and their leader has become a local legend.